Anniversaries - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2010)
Jonas Dautaras. Fosterer of a Child’s Independent Personality Leonas Jovaiša. New Education Systems from Education Historian View Ona Danutė Žilienė. Humanism as a Scientific Guideline